2010
DOI: 10.1116/1.3456619
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metal etch residues on etch species density and uniformity

Abstract: Uniformity and wafer-to-wafer reproducibility of plasma etch processes are often related to the conditioning of the plasma etch chamber walls. For advanced complementary metal-oxide semiconductor fabrication, numerous metals are used which might deposit on the chamber walls during etch processes and as these metals are not always straightforward to remove, process instabilities can occur. This happens because recombination of atomic species on the chamber walls determines to a certain degree the plasma composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Note, etching in chlorine based chemistry is very sensitive to the chamber wall condition [23][24][25]. Chamber pre conditioning with the etch gas composition was performed for 5 min on a silicon wafer, prior to etching actual samples.…”
Section: Methodsmentioning
confidence: 99%
“…Note, etching in chlorine based chemistry is very sensitive to the chamber wall condition [23][24][25]. Chamber pre conditioning with the etch gas composition was performed for 5 min on a silicon wafer, prior to etching actual samples.…”
Section: Methodsmentioning
confidence: 99%
“…3), an atomic concentration of Si:O:Ti ¼ 23:60:17 was obtained. Interestingly, Dictus et al 13 found that after etching of TiN to coat chamber walls with Ti, and then exposing the surface to an O 2 /5%Ar plasma, the optical emission from O atoms, normalized to Ar emission, decreased by 30% relative to that found when the reactor walls were coated with SiO 2 , suggesting an increase in O recombination. The pressure rises recorded for this "17% Ti" surface ( Fig.…”
Section: B Surface Preparation Conditioning and O Recombination Onmentioning
confidence: 99%
“…This feature makes AlF 3 an attractive inorganic resist for electron-beam nanopatterning techniques. , In addition to this, fluorine-rich cleaning discharges can transform chamber interior/mask components made from aluminum into aluminum fluoride, , and that enables application for fabrication of complementary metal oxide semiconductor devices. However, along with the significant study of the decomposition and formation of solid Al–F compounds, formation of Al–F complex molecules is another common phenomenon, and very little information on this topic is available now . Metal fluorides are traditionally prepared by fluorination or other chemical synthesis, such as the plasma chemistry of dry etching method, which involves much more complicated processes exceeding the way that isolated atom or molecule diffuses over a metal surface.…”
Section: Introductionmentioning
confidence: 99%